Fall Risk Increasing Drugs: The Effect on Injuries of the Frail Elderly Estimated from Administrative Data - Thomas K. Bauer; Katharina Lindenbaum; Magdalena A. Stroka; Susanne Ahrens; Roland Linder; Frank Verheyen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Society benefits on a large scale from improved medical care and pharmaceuticals. The prescription of pharmaceuticals, however, also carries risks such as the possibility of an increased risk of falls, which may lead to severe injuries and increased health expenditures associated with these injuries. This study investigates the influence of several fall risk increasing drugs (FRIDs) on the number of injuries of elderly persons using multivariate regression models. Routine data from the Techniker Krankenkasse (TK) of frail elderly persons aged Ï 65 years is analyzed for the year 2009 by estimating count data models, in order to take the data generating process of the number of injuries into account. The results of the count data model are compared to those from logistic regressions, which is the default regression model in this fi eld of research. The empirical results suggest that antidepressants, anxiolytics, hypnotics and sedatives, antiarrhythmics, and drugs from the Priscus-list have a signifi cant positive effect on the number of injuries, while antihypertensives and anti-parkinsonian agents show no and neuroleptics a significant negative eff ect. As recurrent injuries are common, the analysis of the number of injuries rather than just the probability of having an injury provides a more informative analysis of FRIDs. – – Flächendeckende medizinische Versorgung und eine verbesserte Pharamkotherapie haben dazu geführt, dass die Lebenserwartung in den vergangenen Jahrzehnten stetig gestiegen ist. Dennoch ist die Einnahme von Medikamenten nicht ausschließlich nutzenbringend, sondern kann für gewisse Personengruppen mit Risiken und hohen Nachbehandlungskosten einhergehen. Deshalb verwendet diese Studie Routinedaten der Techniker Krankenkasse, um den Einfluss von sturzrisikofördernden Medikamenten, auf die Anzahl von Verletzungen bei älteren Menschen ab einem Alter von 65 Jahren zu untersuchen. Für die Schätzung werden im Gegensatz zur existierenden Literatur anstelle von Logit Modellen, Count Data Modelle verwendet, die die besondere, hier vorliegende Datenstruktur berücksichtigen. Die empirischen Ergebnisse zeigen, dass bestimmte Medikamentengruppen, wie Antidepressiva, Anxiolytika, Hypnotika und Sedativa, Antiarrhythmika sowie Medikamente der Priscus-Liste einen positiv signifikanten Einfluss auf die Anzahl von Verletzungen haben, wohingegen der Einfluss von Antihypertensiva und Antiparkinson Mittel insignifikant ist. Demnach ist vor allem bei der Verschreibung der erstgenannten Medikamentengruppen besondere Vorsicht geboten und eine Abwägung der Risiken und des Nutzen von Nöten.
Keywords: I12; I19; 330; Fall risk increasing drugs; Priscus-List; frail elderly; multivariate regression; count data models; Fall risk increasing drugs; Priscus-List; frail elderly; multivariate regression; count data models